2020
DOI: 10.12688/wellcomeopenres.16293.1
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on public health interventions in the management of the COVID-19 pandemic in Thailand

Abstract: Background: Any government needs to react quickly to a pandemic and make decisions on healthcare interventions locally and internationally with little information regarding the perceptions of people and the reactions they may receive during the implementation of restrictions. Methods: We report an anonymous online survey in Thailand conducted in May 2020 to assess public perceptions of three interventions in the Thai context: isolation, quarantine and social distancing. A total of 1,020 participants, of whom 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…This study finds that the majority of Thai respondents adopted the newly introduced personal protective measures and only 5% indicated that they have never adopted any of these guidelines during the early phase of the pandemic. This corresponds to the findings that indicated 92% of respondents changed their social behavior even before the implementation of government policy in late March, whereby 94% practiced social distancing, 97% used personal protective equipment such as masks and 97% reported using sanitizer products [ 39 ]. Social determinants of marital status, residential area, and degree of worry were found to be associated with the prediction for the adoption rate of personal protective measures in Thailand whereas sex, age, education, and income were found to have no impact.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This study finds that the majority of Thai respondents adopted the newly introduced personal protective measures and only 5% indicated that they have never adopted any of these guidelines during the early phase of the pandemic. This corresponds to the findings that indicated 92% of respondents changed their social behavior even before the implementation of government policy in late March, whereby 94% practiced social distancing, 97% used personal protective equipment such as masks and 97% reported using sanitizer products [ 39 ]. Social determinants of marital status, residential area, and degree of worry were found to be associated with the prediction for the adoption rate of personal protective measures in Thailand whereas sex, age, education, and income were found to have no impact.…”
Section: Discussionsupporting
confidence: 82%
“…Recruitment of respondents was completed via social media platforms using existing personal and social contacts. The snowball technique was chosen because at the time of the data collection, the general public started to be aware of the COVID-19 outbreak and it was not convenient to come in contact with a large population due to safety concerns, especially in March when the cases started to soar [ 39 ]. Inclusion criteria were individuals who resided in Thailand.…”
Section: Methodsmentioning
confidence: 99%
“…Data were collected from 1 st May 2020 to 31 st May 2020 ( Underlying data 13 ). This represents the period in which the number of reported cases in the country was decreasing after the extensive restrictions by the government under the state of emergency announced at the end of April 2020.…”
Section: Methodsmentioning
confidence: 99%
“…We have also conducted a preliminary analysis of unweighted Thai survey responses during May 2020, which includes more detailed breakdowns by regions within Thailand. 66…”
Section: Strengths and Limitationsmentioning
confidence: 99%